DOES DIET START TOMORROW? A DISCOURSE ANALYSIS OF SELF-DEPRECATING HUMOR AGAINST DIET CULTURE IN DIET STARTS TOMORROW - Chaerani, Astrid Restu; Junaidi, Junaidi (Celtic: A Journal of Culture, English Language Teaching, Literature and Linguistics, 2019)
The hegemonic diet culture has recently become ruled out due to its painful methods of losing weight and its bad side effect for health. However, it is hardly denied that many women still put their body weight as a big matter due to the perpetuated portrayal of slim female figures throughout visual media. This article contains a discourse analysis of the Instagram page Diet Starts Tomorrow (@dietstartstomorrow), a humor-branded page reflecting upon female’s daily life that tends to involve diet culture in it throughout textual jokes. Data obtained from numbers of humorous text contain self-criticism, rejection, and circumvention of so-called healthy lifestyle written and posted by mostly female speakers. Through Gramscian lens, it is explored that self deprecating humor articulates young women’s resistance towards the hegemonic diet culture. Self deprecation primarily serves as a comfort space for young women, boosts self-confidence, and creates mutual understanding between audience through unveiling their emotional vulnerability. The results of the study refer to the humorous self-deprecatory text as a critique towards strict diet methods and beauty standards, for example by not judging female who keep consuming junk food or large portions of food. The research suggests further examination on how language is utilized to empower fat movement within the society of both gender.